Początki parafi i Matki Bożej Królowej Korony Polskiej w Baranowiczach poleskich na podstawie księgi inwentarzowej parafi i Baranowicze z 2 maja 1938 roku - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2020)
The Polish Borderland’s town Baranowicze in the county Nowogród (now Bialorus) was developing with resilience from the beginning of the 20. century. The need of a new parish church in the city saw the local bishop, as well as the believers The second parish in the city, after the 1925 founded Hole Cross Exaltation’s parish has been created 1936. It was the Mother of God Quinn’s of Poland parish. It’s pastor became fr. Antoni Kohutnicki. And soon replaced him fr. Czesław Fedorowicz. At that time has been established the Inventor’s Book which is allowing to get knowledge of the beginnings of that parish.